Method of making a catheter

The method for preparing conduits without heat shrink tubing uses a mixture of polyether block polyamide and m-cresol slurry, low-temperature coating, and two-stage heating and curing. This method solves the problems of high material costs and solvent residue in conduit preparation and achieves high-quality finished conduits.

CN123040376APending Publication Date: 2026-11-06TIANJIN PULI ARK MEDICAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611261734.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-19
Publication Date
2026-11-06

AI Technical Summary

Technical Problem

Existing methods for preparing conduits use heat-shrink tubing lamination processes, which result in high material costs and non-recyclability. Heat-shrink tubing is a disposable consumable, and the introduction of volatile organic compounds into the mixed solvent system increases the complexity of solvent residue control and the risk of finished product defects.

Method used

A heat-shrinkable tubing preparation method is adopted, in which polyether block polyamide and m-cresol are mixed by slurry formulation, and the metal skeleton is coated by extruder at low temperature. The product is then cured by heating twice to form the finished product, avoiding solvent residue and improving the interfacial bonding strength.

Benefits of technology

It reduces production costs, improves the density and surface smoothness of finished products, meets the registration and clinical requirements of endoscopic catheters, and reduces solvent residue and finished product defects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123040376A_ABST
    Figure CN123040376A_ABST
Patent Text Reader

Abstract

This invention belongs to the field of medical device manufacturing technology and discloses a method for preparing a catheter, including the following steps: skeleton preparation, selecting a mandrel and winding a metal skeleton around the surface of the mandrel; slurry preparation, mixing polyether block polyamide and m-cresol at a mass ratio of 1:10-1:2 to form a slurry; outer layer preparation, placing the slurry in an extruder and extruding the slurry at a temperature of 50℃-120℃ to coat the metal skeleton, scraping off excess slurry from the surface of the metal skeleton to form a semi-finished product; heat curing, subjecting the semi-finished product to a first heat curing at a first temperature; subjecting the semi-finished product to a second heat curing at a second temperature, the second heating temperature being higher than the first heating temperature; and removing the mandrel from the semi-finished product after the second heat curing to form the finished product. Compared to the heat shrink tubing lamination process, this application does not require the consumption of heat shrink tubing, reducing production costs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of medical device manufacturing technology and relates to a method for preparing a catheter. Background Technology

[0002] Medical endoscope catheters need to travel through extremely narrow spaces (such as bronchi and ureters). Therefore, the catheters need to have a high-strength skeleton (stainless steel / nickel-titanium braided or wound) to prevent collapse; and a flexible outer layer (polyether block polyamide, thermoplastic polyurethane or other thermoplastic elastomers) to protect tissues.

[0003] Typically, the preparation of conduits employs a heat-shrink tubing lamination process: a four-layer structure consisting of an inner tube, a braided or wound skeleton, an outer tube, and a heat-shrink tubing. The outer tube (polyether block polyamide / thermoplastic polyurethane) is fitted over the braided or wound skeleton, and then a fluorinated ethylene propylene copolymer (FEP) heat-shrink tubing is inserted. Heating to 200℃-280℃ causes the heat-shrink tubing to shrink radially, creating a tightening force that laminates the outer tube onto the braided or wound skeleton. After cooling and setting, the heat-shrink tubing is peeled off to obtain the finished product.

[0004] However, heat shrink tubing is a disposable consumable, with high manufacturing costs, and it cannot be recycled and reused, resulting in high material costs and high production costs per piece of tubing. Summary of the Invention

[0005] The purpose of this invention is to provide a method for preparing a conduit. Compared with the heat shrink tubing lamination process, this application does not require the consumption of heat shrink tubing, thus reducing production costs.

[0006] A method for preparing a catheter includes the following steps: Skeleton preparation involves selecting a mandrel and winding a metal skeleton around the surface of the mandrel. Slurry preparation: Polyether block polyamide and m-cresol are mixed at a mass ratio of 1:10-1:2 to form a slurry; To prepare the outer layer, the slurry is placed in an extruder and extruded at a temperature of 50℃-120℃ to coat the metal skeleton. Excess slurry on the surface of the metal skeleton is scraped off to form a semi-finished product. The semi-finished product is subjected to heat curing at a first curing temperature; and then subjected to heat curing at a second curing temperature, wherein the second curing temperature is higher than the first curing temperature. The mandrel is removed from the semi-finished product after a second heating and curing process to form the finished product.

[0007] In some embodiments, the solvent in the slurry is only m-cresol, without acetone or other auxiliary solvents. In some implementations, the total duration of the first heat curing and the second heat curing is 8 to 15 minutes.

[0008] In some embodiments, during the first and second heat curing processes, the semi-finished product is placed in an oven for heating, and the mandrel is also heated at a temperature 5°C-10°C higher than that of the oven.

[0009] In some implementations, the mandrel is made of metal and is connected to the power source to form a current loop for heating.

[0010] In some embodiments, the metal skeleton is woven or wound from metal wires. When the metal wires are round, the diameter is 0.03mm-0.15mm. When the metal wires are flat, the thickness is 0.03mm-0.15mm and the width is 0.05mm-0.20mm. The density of the metal wires woven or wound is 60PPI-150PPI.

[0011] In some implementations, the slurry mixing step, the outer layer preparation step, and the heating and curing step are repeated at least twice.

[0012] In some embodiments, a vacuum pump is connected below the extruder to provide a vacuum of 0.05 MPa to 0.08 MPa during slurry extrusion.

[0013] In some embodiments, the mandrel surface is mirror-polished and coated with a Teflon or titanium nitride anti-stick layer.

[0014] In some embodiments, a hydrophilic coating is applied to the surface of the finished product, followed by UV curing.

[0015] The catheter preparation method provided in this application includes the following steps: skeleton preparation, selecting a mandrel and winding a metal skeleton around the surface of the mandrel; slurry preparation, mixing polyether block polyamide and m-cresol at a mass ratio of 1:10-1:2 to form a slurry; outer layer preparation, placing the slurry in an extruder and extruding the slurry at a temperature of 50℃-120℃ to coat the metal skeleton, scraping off excess slurry from the surface of the metal skeleton to form a semi-finished product; heat curing, subjecting the semi-finished product to a first heat curing at a first temperature; subjecting the semi-finished product to a second heat curing at a second temperature, the second heating temperature being higher than the first heating temperature; and removing the mandrel from the semi-finished product after the second heat curing to form the finished product. The finished product of this application has a smooth surface, is free of bubbles and peeling, has a dense structure, and shows no cracks, delamination, or exposed metal wires after a bending test, meeting the mainstream registration and clinical requirements for endoscopic catheters. Compared to the heat shrink tubing lamination process, this application does not require heat shrink tubing, thus reducing production costs. Furthermore, this application effectively reduces the residue of m-cresol in the finished product through a first heating curing and a second heating curing. Attached Figure Description

[0016] Figure 1 A flowchart illustrating the catheter preparation method provided in this application embodiment. Detailed Implementation

[0017] The following specific embodiments further illustrate the technical solution of the present invention. These specific embodiments do not represent a limitation on the scope of protection of the present invention. Non-essential modifications and adjustments made by others based on the concept of the present invention still fall within the scope of protection of the present invention.

[0018] The catheter is manufactured using a heat-shrink tubing lamination process: a four-layer structure consisting of an inner tube, a braided or wound skeleton, an outer tube, and a heat-shrink tubing. The outer tube material includes polyether block polyamide (PEBA) and / or thermoplastic polyurethane (TPU), which is fitted over the braided or wound skeleton. Fluorinated ethylene propylene copolymer (FEP) heat-shrink tubing is then inserted onto the outside. Heating to 200℃-280℃ causes the heat-shrink tubing to shrink radially, creating a tightening force that laminates the outer tube onto the braided or wound skeleton. After cooling and setting, the heat-shrink tubing is peeled off to obtain the finished product. However, heat-shrink tubing is a disposable consumable, resulting in high manufacturing costs. Furthermore, heat-shrink tubing cannot be recycled and reused, leading to high material and production costs per catheter.

[0019] Furthermore, in existing catheter fabrication technologies, there is a scheme that uses polyether block polyamide and a mixed solvent (such as a mixture of acetone and m-cresol) to formulate the slurry. Although this scheme can reduce the viscosity of the slurry to some extent, the mixed solvent system introduces various volatile organic compounds, increasing the complexity of controlling the total solvent residue. Moreover, low-boiling-point solvents such as acetone are prone to forming bubbles and voids during the heating and curing process, leading to defects inside the finished product and failure of the interface between the metal skeleton and the outer layer of the polyether block polyamide.

[0020] To address the aforementioned problems, this application employs a method for preparing a catheter, comprising the following steps: S1. Skeleton preparation: Select a mandrel and wrap a metal skeleton around the surface of the mandrel; S2. Slurry preparation: Polyether block polyamide (PEBA) and m-cresol are mixed at a mass ratio of 1:10-1:2 to form a slurry. S3. Prepare the outer layer by putting the slurry into the extruder and extruding the slurry at a temperature of 50℃-120℃ and coating it onto the metal skeleton. Scrape off the excess slurry on the surface of the metal skeleton to form a semi-finished product. S4. Heating and curing: The semi-finished product is first heated and cured at a first temperature; the semi-finished product after the first heating is then heated and cured a second time at a second temperature, with the second heating temperature being higher than the first heating temperature. S5. Remove the mandrel from the semi-finished product after the second heating and curing to form the finished product.

[0021] It should be understood that in the skeleton preparation step, the selection of the mandrel is based on the required diameter of the catheter. The surface of the mandrel is wrapped with a metal skeleton. The material of the metal skeleton can be stainless steel or nickel-titanium alloy wire, etc. This application does not impose any restrictions. The metal skeleton provides radial support and anti-kink properties for the catheter.

[0022] In the slurry preparation step, polyether block polyamide and m-cresol are mixed at a mass ratio of 1:10 to 1:2 to form a slurry. The mass ratio of polyether block polyamide to m-cresol can be 1:10, 1:9, 1:8, 1:7, 1:6, 1:5, 1:4, 1:3, or 1:2, etc., and this application does not impose any limitation. The PEBA is a polyether amide elastomer, such as one or more of the Pebax® series from Arkema, including 2533, 3533, 4533, 6333, or 7233. The specific model is selected according to the required hardness of the catheter. The purity of the m-cresol is ≥99.0% to reduce impurities in the finished product. The interaction mechanism of m-cresol and PEBA includes: (1) breaking the hydrogen bonds between PEBA molecules, reducing the viscosity of the system, and making PEBA form a low-viscosity homogeneous fluid at a lower temperature; (2) improving the interfacial bonding - m-cresol increases the polarity of the system. Since the surface of the metal skeleton is polar, the slurry with added m-cresol can significantly improve the wettability of the metal skeleton, and form physical anchoring and chemical adsorption in subsequent curing.

[0023] This invention uses m-cresol as a single solvent, eliminating the need for auxiliary solvents such as acetone, to achieve low-viscosity extrusion of the slurry and full impregnation of the skeleton. At the same time, through the synergistic effect of low-temperature pre-evaporation and high-temperature deep removal, solvent residue is effectively reduced and a dense conduit structure is obtained.

[0024] In the outer layer preparation step, the slurry is placed in a solvent-modified extruder and extruded at 50℃–120℃ to coat the outer surface of the metal skeleton. Excess slurry is then scraped off the surface of the metal skeleton to form a semi-finished product. The extruder temperature is preferably 50℃, 60℃, 70℃, 80℃, 90℃, 100℃, 110℃, or 120℃. Due to the addition of m-cresol, the slurry dissolution temperature is significantly reduced, allowing for processing at low temperatures. This prevents both the thermal degradation of PEBA and the excessively rapid volatilization of m-cresol.

[0025] After the slurry is extruded from the extruder, it coats the outer surface of the metal skeleton in a top-to-bottom direction. Gravity assists the slurry flow, and under the action of m-cresol, the slurry viscosity decreases (20 Pa·s-100 Pa·s). Under the extrusion pressure (0.5 MPa-2 MPa), it can quickly penetrate the mesh of the metal skeleton and reach the inner lining surface, achieving "zero void" filling. Furthermore, with the micro-supply from the die of the extruder (gap 0.05 mm-0.15 mm), a relatively thin coating is initially formed (wet thickness after extrusion 0.3 mm-0.5 mm).

[0026] After the slurry coats the outside of the metal frame, a scraping and sizing device is used. This device includes precision through-holes (hole diameter = target outer diameter, material is ceramic or hard alloy, surface mirror polished, roughness Ra less than or equal to 0.2μm). As the uncured slurry passes through the through-holes, excess material is physically scraped off, ensuring precise and consistent pipe outer diameter. Simultaneously, by adjusting the matching of the traction speed and extrusion speed (speed ratio 1.0-1.2), precise and consistent pipe outer diameter is ensured. The removal of excess slurry forms a semi-finished product.

[0027] In the heat curing step, the semi-finished product is heated for the first time at the first curing temperature. The m-cresol is in a sub-boiling state, and the kinetic energy of the m-cresol solvent molecules is sufficient to diffuse to the surface but not enough to violently vaporize and break through the surface layer. This avoids the surface polymer drying too quickly, forming a "hard shell" (skin effect) that would block the internal solvent channels, ensuring that the internal channels remain open for continuous migration of deeper solvents. At the second curing temperature, the semi-finished product is heated a second time. The second curing temperature is higher than the first curing temperature, allowing for deeper removal of m-cresol. Furthermore, the second curing temperature is near the softening point of the polyether block polyamide, causing a sudden increase in polymer chain mobility. This releases the deep solvent molecules locked by hydrogen bonds, while simultaneously promoting molecular chain rearrangement and recrystallization, forming a dense structure.

[0028] After the first and second heat curing processes, the semi-finished product is mechanically removed from the mandrel to form the finished product. The finished product of this application has a smooth surface, free of bubbles and peeling. After bending test (referring to GB / T 15812.1-2005), the bent part showed no cracks, delamination, or exposed metal wires, meeting mainstream registration and clinical requirements.

[0029] In some optional embodiments, the first curing temperature is 80℃-120℃, and the first curing time is 5 minutes-10 minutes. The first curing temperature can be 80℃, 90℃, 100℃, 110℃, or 120℃, and this application is not limited thereto. The first curing time can be 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes, or 10 minutes, and this application is not limited thereto. When the first curing temperature is below 80℃, the molecular chain mobility is insufficient, the solvent molecule diffusion rate is low, and the m-cresol removal efficiency decreases. When the first curing temperature is above 120℃, the solvent molecules vaporize violently, easily breaking through the surface polymer and forming surface defects. When the first curing time is less than 5 minutes, the m-cresol diffusion is insufficient, and the solvent residue is too high. When the first curing time exceeds 10 minutes, the surface PEBA cures prematurely, forming a dense shell layer, which hinders the continued outward diffusion of internal m-cresol, thereby causing internal solvent residue, local voids or microbubble aggregation, and uneven shrinkage of the conduit wall thickness, and even inducing interface debonding or microcracks.

[0030] In some optional embodiments, the second curing temperature is 140℃-200℃, and the second curing time is 3 minutes-10 minutes. The second curing temperature can be 140℃, 150℃, 160℃, 170℃, 180℃, 190℃, or 200℃, and this application is not limited thereto. The second curing time can be 3 minutes, 4 minutes, 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes, or 10 minutes, and this application is not limited thereto. When the second curing temperature is below 140℃, the molecular chain mobility is insufficient, and the m-cresol removal efficiency is low. When the second curing temperature is above 200℃, the polyether block is overheated, the soft segment polyether chain (PTMG) undergoes thermal oxidative breakage, the hard segment polyamide over-crystallizes, the molecular weight decreases, the melt strength deteriorates, and the risk of cytotoxicity increases. When the second curing time is less than 3 minutes, the removal of m-cresol is incomplete, resulting in a high residual amount. When the second curing time exceeds 10 minutes, combined with the first curing time, the total heating time easily exceeds the safety threshold, leading to accelerated thermal oxidative degradation of PEBA segments, excessive crystallization of hard segments, and destruction of the microphase separation structure. This manifests as decreased mechanical properties and increased cytotoxicity risk. Furthermore, experiments show that the residual amount of m-cresol tends to reach removal equilibrium within the range of 8–10 minutes, and further extending the time has minimal marginal contribution, instead increasing energy consumption and production cycle, which is detrimental to industrialization.

[0031] In some optional embodiments, the total curing time for the first and second curing is 8-15 minutes. The total curing time can be 8, 9, 10, 11, 12, 13, 14, or 15 minutes, and this application does not impose any limitation. When the total curing time is less than 8 minutes, m-cresol removal is insufficient, the residual solvent content in the finished product increases significantly, the interface between the metal skeleton and the outer layer of the polyether block polyamide fails, and biocompatibility risks such as cytotoxicity and sensitization may occur. When the total curing time is greater than 15 minutes, the polyether block polyamide (PEBA) molecular chains are continuously heated for a longer period, the thermal oxidative degradation of the polyether segments with PTMG as the soft segment intensifies, leading to molecular chain breakage, yellowing, and embrittlement of the material; simultaneously, the PA12 hard segment undergoes secondary crystallization or slight cross-linking, and the microphase separation structure is destroyed, causing the polyether block polyamide (PEBA) to lose its thermoplastic elastomer characteristics. The aforementioned structural degradation manifests as a decline in mechanical properties, including the failure of the interfacial bonding between the metal skeleton and the outer layer of the polyether block polyamide, and a decrease in tensile elongation at break. Furthermore, byproducts such as aldehydes, ketones, and peroxides generated from the thermal oxidative degradation of the soft segments possess potential cytotoxicity, increasing the risk of biocompatibility issues. On the other hand, experiments show that the removal of m-cresol residues reaches equilibrium within the 8-15 minute range; further extending the heating time has minimal marginal contribution to reducing residue levels, and instead leads to increased energy consumption and decreased production efficiency, hindering industrialization.

[0032] In some optional embodiments, during the heat curing process, the semi-finished product is placed in an oven for heating, and the mandrel is simultaneously heated. The mandrel temperature is 5°C-10°C higher than the oven temperature. Mandrel heating allows for simultaneous heating of the interior of the semi-finished product, ensuring uniform heating along the wall thickness direction, improving the removal efficiency of m-cresol and the densification effect of PEBA, while shortening the heating time. The mandrel temperature being 5°C-10°C higher than the oven temperature can be 5°C, 6°C, 7°C, 8°C, 9°C, or 10°C, etc., and this application is not limited to this. This can compensate for the thermal resistance along the wall thickness direction of the conduit, achieve radial temperature field homogenization, promote the outward diffusion of m-cresol from the inner wall, reduce internal solvent residue, avoid thermal degradation of polyether block polyamide (PEBA) caused by overheating of the outer wall, promote the synchronous formation of a dense structure of polyether block polyamide (PEBA) from the inside out, reduce uneven thermal shrinkage, and avoid inducing interfacial debonding or microcracks.

[0033] In some alternative embodiments, the mandrel is made of metal and is connected to a power source to form a resistance heating circuit. By adjusting the current, the mandrel temperature can be precisely controlled, thereby controlling the internal heating temperature of the semi-finished product, facilitating temperature control by the operator and improving heating uniformity.

[0034] In some optional embodiments, the metal skeleton is woven or wound from metal wires. When the metal wires are round, their diameter is 0.03mm-0.15mm; when they are flat, their thickness is 0.03mm-0.15mm and their width is 0.05mm-0.20mm. The density of the metal wires during weaving or winding is 60PPI-150PPI. The metal wires can be stainless steel or nickel-titanium alloy wires, etc., and this application does not impose any limitations. When the metal wire is round, its diameter can be 0.03mm, 0.04mm, 0.05mm, 0.06mm, 0.07mm, 0.08mm, 0.09mm, 0.1mm, 0.11mm, 0.12mm, 0.13mm, 0.14mm, 0.15mm, etc., which are not limited in this application. When the metal wire is flat, its thickness can be 0.03mm, 0.04mm, 0.05mm, 0.06mm, 0.07mm, 0.08mm, 0.09mm, 0.1mm, 0.11mm, 0.12mm, 0.13mm, 0.14mm, 0.15mm, etc., which are not limited in this application. Its width can be 0.05mm, 0.06mm, 0.07mm, 0.08mm, 0.09mm, 0.1mm, 0.15mm, 0.2mm, etc., which are not limited in this application. The density of the metal wire during braiding or winding can be 60 PPI, 70 PPI, 80 PPI, 90 PPI, 100 PPI, 110 PPI, 120 PPI, 130 PPI, 140 PPI, 150 PPI, etc., and this application does not impose any limitation. Since the thickness or diameter of the metal wire can reach 0.03 mm, the thinnest thickness of the conduit can be 0.03 mm.

[0035] In some optional embodiments, the slurry mixing step, the outer layer coating step, and the heat curing step are repeated at least twice. When it is necessary to prepare a conduit with a thicker wall, the slurry mixing step, the outer layer coating step, and the heat curing step can be repeated again. In the second operation, the slurry ratio can be changed to adjust the hardness and performance of the conduit, or the slurry from the first operation can be used. This application does not impose any restrictions, and the specific number of repetitions can be set according to the wall thickness requirements.

[0036] In some alternative embodiments, a vacuum pump is connected below the extruder, maintaining a vacuum of 0.05 MPa to 0.08 MPa during slurry extrusion. Vacuum levels are 0.05 MPa, 0.06 MPa, 0.07 MPa, or 0.08 MPa. During the outer layer preparation step, negative pressure suction can be used to force the low-viscosity polyether block polyamide / m-cresol slurry into an extremely dense micro-wire braided layer (e.g., 150 PPI ultra-high density braid), eliminating microbubbles and improving filler content.

[0037] In some optional embodiments, the mandrel surface is mirror-polished and coated with a Teflon or titanium nitride anti-stick layer. The mandrel surface is mirror-polished (Ra less than or equal to 0.4 μm) and coated with a Teflon or titanium nitride anti-stick layer to facilitate subsequent demolding.

[0038] In some alternative embodiments, a hydrophilic coating is applied to the surface of the finished product, followed by UV curing. This reduces the coefficient of friction of the catheter, improves its ease of insertion into the human body, and reduces harm to the body.

[0039] Example Example 1 S1. Skeleton preparation: Select a mandrel, which is a metal mandrel, and wrap a metal skeleton around the surface of the mandrel. The metal mandrel is then mirror-polished and coated with Teflon. S2. Slurry preparation: Polyether block polyamide (trade name Pebax) and m-cresol are mixed at a mass ratio of 1:4 to form a slurry. S3. Prepare the outer layer by putting the slurry into the extruder and extruding the slurry at a temperature of 50°C to coat the metal skeleton. Use a precision scraping and sizing device with a 0.65mm aperture to scrape off the excess slurry on the surface of the metal skeleton to form a semi-finished product. S4. Heat curing: At the first temperature, the semi-finished product is heat-cured for 5 minutes, with the oven temperature at 80℃ and the mandrel temperature at 85℃; at the second temperature, the semi-finished product after the first heat is heat-cured for 3 minutes, with the oven temperature at 140℃ and the mandrel temperature at 145℃. S5. Remove the mandrel from the semi-finished product after the second heating and curing to form the finished product. Coat the surface of the finished product with a hydrophilic coating and then perform ultraviolet curing.

[0040] Example 2 S1. Skeleton preparation: Select a mandrel, which is a metal mandrel, and wrap a metal skeleton around the surface of the mandrel. The metal mandrel is then mirror-polished and coated with Teflon. S2. Slurry preparation: Polyether block polyamide (trade name Pebax) and m-cresol are mixed at a mass ratio of 1:4 to form a slurry. S3. Prepare the outer layer by putting the slurry into the extruder and extruding the slurry at a temperature of 80°C to coat the metal skeleton. Use a precision scraping and sizing device with a 0.65mm aperture to scrape off the excess slurry on the surface of the metal skeleton to form a semi-finished product. S4. Heat curing: At the first temperature, the semi-finished product is heat-cured for 8 minutes, with the oven temperature at 100℃ and the mandrel temperature at 108℃; at the second temperature, the semi-finished product after the first heat is heat-cured for 5 minutes, with the oven temperature at 160℃ and the mandrel temperature at 168℃. S5. Remove the mandrel from the semi-finished product after the second heating and curing to form the finished product. Coat the surface of the finished product with a hydrophilic coating and then perform ultraviolet curing.

[0041] Example 3 S1. Skeleton preparation: Select a mandrel, which is a metal mandrel, and wrap a metal skeleton around the surface of the mandrel. The metal mandrel is then mirror-polished and coated with Teflon. S2. Slurry preparation: Polyether block polyamide (trade name Pebax) and m-cresol are mixed at a mass ratio of 1:4 to form a slurry. S3. Prepare the outer layer by putting the slurry into the extruder and extruding the slurry at a temperature of 120°C to coat the metal skeleton. Use a precision scraping and sizing device with a 0.65mm aperture to scrape off the excess slurry on the surface of the metal skeleton to form a semi-finished product. S4. Heat curing: At the first temperature, the semi-finished product is heat-cured for 5 minutes, with the oven temperature at 120℃ and the mandrel temperature at 125℃; at the second temperature, the semi-finished product after the first heat is heat-cured for 10 minutes, with the oven temperature at 200℃ and the mandrel temperature at 205℃. S5. Remove the mandrel from the semi-finished product after the second heating and curing to form the finished product. Coat the surface of the finished product with a hydrophilic coating and then perform ultraviolet curing.

[0042] Example 4 S1. Skeleton preparation: Select a mandrel, which is a metal mandrel, and wrap a metal skeleton around the surface of the mandrel. The metal mandrel is then mirror-polished and coated with Teflon. S2. Slurry preparation: Polyether block polyamide and m-cresol are mixed at a mass ratio of 1:2 to form a slurry. S3. Prepare the outer layer by putting the slurry into the extruder and extruding the slurry at a temperature of 100°C to coat the metal skeleton. Use a precision scraping and sizing device with a 0.65mm aperture to scrape off the excess slurry on the surface of the metal skeleton to form a semi-finished product. S4. Heat curing: At the first temperature, the semi-finished product is heat-cured for 7 minutes, with the oven temperature at 90℃ and the mandrel temperature at 100℃; at the second temperature, the semi-finished product after the first heat is heat-cured for 6 minutes, with the oven temperature at 170℃ and the mandrel temperature at 180℃. S5. Remove the mandrel from the semi-finished product after the second heating and curing to form the finished product. Coat the surface of the finished product with a hydrophilic coating and then perform ultraviolet curing.

[0043] Example 5 S1. Skeleton preparation: Select a mandrel, which is a metal mandrel, and wrap a metal skeleton around the surface of the mandrel. The metal mandrel is then mirror-polished and coated with Teflon. S2. Slurry preparation: Polyether block polyamide and m-cresol are mixed at a mass ratio of 1:10 to form a slurry. S3. Prepare the outer layer by putting the slurry into the extruder and extruding the slurry at a temperature of 50°C to coat the metal skeleton. Use a precision scraping and sizing device with a 0.65mm aperture to scrape off the excess slurry on the surface of the metal skeleton to form a semi-finished product. S4. Heat curing: At the first temperature, the semi-finished product is heat-cured for 10 minutes, with the oven temperature at 95℃ and the mandrel temperature at 105℃; at the second temperature, the semi-finished product after the first heat is heat-cured for 5 minutes, with the oven temperature at 165℃ and the mandrel temperature at 175℃. S5. Remove the mandrel from the semi-finished product after the second heating and curing to form the finished product. Coat the surface of the finished product with a hydrophilic coating and then perform ultraviolet curing.

[0044] Example 6 S1. Skeleton preparation: Select a mandrel, which is a metal mandrel, and wrap a metal skeleton around the surface of the mandrel. The metal mandrel is then mirror-polished and coated with Teflon. S2. Slurry preparation: Polyether block polyamide and m-cresol are mixed at a mass ratio of 1:4 to form a slurry. S3. Prepare the outer layer by putting the slurry into the extruder and extruding the slurry at a temperature of 80°C to coat the metal skeleton. Use a precision scraping and sizing device with a 0.65mm aperture to scrape off the excess slurry on the surface of the metal skeleton to form a semi-finished product. S4. Heat curing: At the first temperature, the semi-finished product is heat-cured for 10 minutes, with the oven temperature at 95℃ and the mandrel temperature at 105℃; at the second temperature, the semi-finished product after the first heat is heat-cured for 5 minutes, with the oven temperature at 165℃ and the mandrel temperature at 175℃. S5. Re-formulate the slurry: Mix polyether block polyamide and m-cresol at a mass ratio of 1:5 to form a slurry; S6. Put the newly prepared slurry into the extruder and extrude the slurry at a temperature of 80°C and coat it onto the surface of the semi-finished product that has been heated and cured for the second time. Use a precision scraping and sizing device with a 0.65mm aperture to scrape off the excess slurry on the surface. S7. Heat curing: At the first temperature, the semi-finished product coated with the new slurry is heated and cured for a third time for 10 minutes. The oven temperature is 95℃ and the mandrel temperature is 105℃. At the second temperature, the semi-finished product after the third heating is heated and cured for a fourth time for 5 minutes. The oven temperature is 165℃ and the mandrel temperature is 175℃. S8. Remove the mandrel from the semi-finished product after the fourth heating and curing to form the finished product. Coat the surface of the finished product with a hydrophilic coating and then perform ultraviolet curing.

[0045] Comparative Example Comparative Example 1 S1. Skeleton preparation: Select a mandrel, which is a metal mandrel, and wrap a metal skeleton around the surface of the mandrel. The metal mandrel is then mirror-polished and coated with Teflon. S2. Slurry preparation: Polyether block polyamide (trade name Pebax) and m-cresol are mixed at a mass ratio of 1:4 to form a slurry. S3. Prepare the outer layer by putting the slurry into the extruder and extruding the slurry at a temperature of 80°C to coat the metal skeleton. Use a precision scraping and sizing device with a 0.65mm aperture to scrape off the excess slurry on the surface of the metal skeleton to form a semi-finished product. S4. Heat curing: The semi-finished product is heat-cured for 15 minutes only at an oven temperature of 160℃. S5. Remove the mandrel from the semi-finished product after heat curing to form the finished product. Coat the surface of the finished product with a hydrophilic coating and then cure it with ultraviolet light.

[0046] Comparative Example 2 S1. Skeleton preparation: Select a mandrel, which is a metal mandrel, and wrap a metal skeleton around the surface of the mandrel. The metal mandrel is then mirror-polished and coated with Teflon. S2. Slurry preparation: Polyether block polyamide (trade name Pebax) and m-cresol are mixed at a mass ratio of 1:4 to form a slurry. S3. Prepare the outer layer by putting the slurry into the extruder and extruding the slurry at a temperature of 80°C to coat the metal skeleton. Use a precision scraping and sizing device with a 0.65mm aperture to scrape off the excess slurry on the surface of the metal skeleton to form a semi-finished product. S4. Heat curing: Heat the semi-finished product for 15 minutes at an oven temperature of 160℃ and a mandrel temperature of 170℃. S5. Remove the mandrel from the semi-finished product after heat curing to form the finished product. Coat the surface of the finished product with a hydrophilic coating and then cure it with ultraviolet light.

[0047] Comparative Example 3 S1. Skeleton preparation: Select a mandrel, which is a metal mandrel, and wrap a metal skeleton around the surface of the mandrel. The metal mandrel is then mirror-polished and coated with Teflon. S2. Slurry preparation: Mix polyether block polyamide (trade name Pebax) and m-cresol at a mass ratio of 1:4 to form a slurry; S3. Prepare the outer layer: put the slurry into the extruder and extrude the slurry at a temperature of 80°C to coat the metal skeleton. Use a precision scraping and sizing device with a 0.65mm aperture to scrape off the excess slurry on the surface of the metal skeleton to form a semi-finished product. S4. Heat curing: At the first temperature, the semi-finished product is heat-cured for 8 minutes at 100°C in the oven without heating the mandrel; at the second temperature, the semi-finished product after the first heating is heat-cured for 5 minutes at 160°C in the oven without heating the mandrel. S5. Remove the mandrel from the semi-finished product after the second heating and curing to form the finished product. Coat the surface of the finished product with a hydrophilic coating and then perform ultraviolet curing.

[0048] Comparative Example 4 S1. Skeleton preparation: Select a mandrel, which is a metal mandrel, and wrap a metal skeleton around the surface of the mandrel. The metal mandrel is then mirror-polished and coated with Teflon. S2. Slurry preparation: Polyether block polyamide (trade name Pebax) and solvent are mixed at a mass ratio of 1:4 to form a slurry. The solvent is a mixed solution of acetone and m-cresol, and the volume ratio of acetone and m-cresol is 1:1. S3. Prepare the outer layer: put the slurry into the extruder and extrude the slurry at a temperature of 80°C to coat the metal skeleton. Use a precision scraping and sizing device with a 0.65mm aperture to scrape off the excess slurry on the surface of the metal skeleton to form a semi-finished product. S4. Heat curing: At the first temperature, the semi-finished product is heat-cured for 8 minutes, with the oven temperature at 100℃ and the mandrel temperature at 108℃; at the second temperature, the semi-finished product after the first heat is heat-cured for 5 minutes, with the oven temperature at 160℃ and the mandrel temperature at 168℃.

[0049] S5. Remove the mandrel from the semi-finished product after the second heating and curing to form the finished product. Coat the surface of the finished product with a hydrophilic coating and then perform ultraviolet curing.

[0050] Example of effect The chemical quantitative determination of m-cresol residues was performed by gas chromatography-mass spectrometry (GC-MS) (HP-5MS column, temperature program: 40℃ for 2 min, then increased to 250℃ at 10℃ / min). The limit of detection (LOD) was 0.001% (10 ppm), and the limit of quantification (LOQ) was 0.003%. Quantification was based on peak area normalization.

[0051] The permissible limit for m-cresol was determined based on the toxicological assessment method in GB / T 16886.17 / ISO 10993-17 "Determination of permissible limits for leachable materials".

[0052] The finished catheters were evaluated for biological safety according to ISO 10993-5 (cytotoxicity) and ISO 10993-10 (irritation and sensitization). This evaluation was conducted on the whole extract of the finished catheters, rather than directly quantifying m-cresol residues.

[0053] Porosity was tested using cross-sectional microscopic image analysis (metallurgical microscope / SEM + ImageJ image analysis) or Micro-CT non-destructive three-dimensional scanning.

[0054] The surface condition of the finished product is judged by visual inspection (2.5x magnification) and optical microscope observation (20-50x, quantifying bubble size and number); The interfacial bonding quality between the metal skeleton and the polyether block polyamide outer layer was evaluated using a bending test. The specific method involved bending the finished conduit 180° with a mandrel diameter five times the outer diameter of the conduit. After release, visual inspection and optical microscopy (20-50x magnification) were used to determine the presence of cracks, delamination, or exposed metal wires at the bent area. If the bent area was smooth, without cracks or exposed metal wires, the interfacial bonding was considered good; if bulges, cracks, or exposed metal wires appeared, debonding or structural defects were identified at the interface.

[0055] Table 1 Test Results

[0056] As shown in Table 1, the residual m-cresol in Examples 1-6 was low (0.002%-0.008%), and the total solvent residue was basically consistent with the residual m-cresol (pure m-cresol system), both far below the permissible limit derived from toxicological assessment. The surface was smooth, without bubbles or peeling. Through bending tests, the finished catheters of Examples 1-6, after being bent 180° with a mandrel diameter 5 times the catheter outer diameter, showed smooth surfaces, no cracks, no delamination, and no exposed metal wires upon release, indicating good interfacial bonding and meeting the mainstream registration and clinical requirements for endoscopic catheters.

[0057] Furthermore, it can be seen that Example 3 has the lowest m-cresol residue, the lowest total solvent residue, the lowest porosity, and meets the standards for skin condition and bending test. Therefore, it can be deduced that the best product is prepared when the mass ratio of polyether block polyamide (trade name Pebax) to m-cresol is 1:4, and the extruder is used at a temperature of 120°C, the first curing time is 5 minutes, the oven temperature is 120°C, and the mandrel temperature is 125°C; the second curing time is 10 minutes, the oven temperature is 200°C, and the mandrel temperature is 205°C.

[0058] As can be seen from the setup of Example 6, by repeatedly setting the slurry proportioning step, the outer layer preparation step, and the heating and curing step, the requirements can still be met even if the wall thickness of the conduit is increased using the method of this application.

[0059] Comparative Example 1 was cured using a single-temperature, one-step heating process (160°C, 15 minutes), resulting in a m-cresol residue of 0.015%. Due to the lack of a two-step gradient heating process and simultaneous heating of the mandrel, solvent removal efficiency was insufficient, leading to a higher internal solvent residue. Bending tests revealed slight bulging at the bent areas, with some areas showing a tendency for exposed metal wires, indicating inferior interfacial bonding quality compared to Examples 1-6.

[0060] Comparative Example 2, based on the single-temperature one-step heating and curing method, added mandrel heating (mandrel temperature 170°C), reducing the m-cresol residue to 0.01%, but still higher than Examples 1-6. Bending test results showed no cracks at the bending points, but slight bubble bulging was present. The interfacial bonding quality was better than Comparative Example 1, but still did not reach the densification level of Examples 1-6.

[0061] Comparative Example 3, although employing a two-step gradient heating process (first curing heating and second curing heating), did not heat the mandrel. The residual m-cresol content was 0.012%, and bubbles and peeling appeared on the surface. Due to uneven heating along the wall thickness, the internal solvent migration channels were blocked, causing the surface m-cresol to evaporate too quickly, forming a hard shell. Internal solvent retention led to surface defects. Bending tests showed cracks at the bending points, localized exposure of metal wires, and significant debonding at the interface, failing to meet clinical use requirements.

[0062] Comparative Example 4 used a mixed solvent of acetone and m-cresol (volume ratio 1:1). Although the residual amount of m-cresol was controlled at 0.008%, the acetone rapidly evaporated during heating, forming bubbles, resulting in a total solvent residue as high as 0.26%, with internal bubbles and voids present. Bending tests showed that cracks appeared at the bending points, exposing the metal wire and indicating interfacial bonding failure. These results verified the technical problem of structural defects caused by the vaporization of low-boiling-point solvents breaking through the surface in mixed solvent systems, and also demonstrated the technical advantages of this invention using a single m-cresol solvent system combined with a two-step gradient heating curing process.

[0063] Method Validation It is understood that the present invention has been described through some embodiments, and those skilled in the art will recognize that various changes or equivalent substitutions can be made to these features and embodiments without departing from the spirit and scope of the invention. Furthermore, under the teachings of the present invention, these features and embodiments can be modified to adapt to specific situations and materials without departing from the spirit and scope of the invention. Therefore, the present invention is not limited to the specific embodiments disclosed herein, and all embodiments falling within the scope of the claims of this application are within the protection scope of the present invention.

Claims

1. A method of making a catheter, characterized by, Includes the following steps: Skeleton preparation involves selecting a mandrel and winding a metal skeleton around the surface of the mandrel. Slurry preparation: Polyether block polyamide and m-cresol are mixed at a mass ratio of 1:10-1:2 to form a slurry; To prepare the outer layer, the slurry is placed in an extruder and extruded at a temperature of 50℃-120℃ to coat the metal skeleton. Excess slurry on the surface of the metal skeleton is scraped off to form a semi-finished product. The semi-finished product is subjected to heat curing at a first curing temperature; and then subjected to heat curing at a second curing temperature, wherein the second curing temperature is higher than the first curing temperature. The mandrel is removed from the semi-finished product after a second heating and curing process to form the finished product.

2. The method for preparing the catheter as described in claim 1, characterized in that, The first curing temperature is 80℃-120℃, the first heating and curing time is 5 minutes-10 minutes, the second curing temperature is 140℃-200℃, and the second heating and curing time is 3 minutes-10 minutes.

3. The method for preparing the catheter as described in claim 2, characterized in that, The total time for the first and second heat curing processes is 8 to 15 minutes.

4. The method for preparing the catheter as described in claim 1, characterized in that, The mandrel is made of metal and is connected to the power source to form a current loop for heating.

5. The method for preparing the catheter as described in claim 4, characterized in that, During the first and second heating and curing processes, the semi-finished product is placed in an oven for heating, while the mandrel is heated at the same time. The temperature of the mandrel is 5°C-10°C higher than the temperature of the oven.

6. The method for preparing the catheter as described in claim 1, characterized in that, The metal skeleton is woven or wound from metal wires. When the metal wires are round, the diameter is 0.03mm-0.15mm. When the metal wires are flat, the thickness is 0.03mm-0.15mm and the width is 0.05mm-0.20mm. The density of the metal wires woven or wound is 60PPI-150PPI.

7. The method for preparing the catheter as described in claim 1, characterized in that, The slurry mixing step, the outer layer preparation step, and the heating and curing step are repeated at least twice.

8. The method for preparing the catheter as described in claim 1, characterized in that... A vacuum pump is connected below the extruder, and the vacuum level is 0.05MPa-0.08MPa when extruding the slurry.

9. The method for preparing the catheter as described in claim 1, characterized in that, The mandrel surface is mirror-polished and coated with a Teflon or titanium nitride anti-stick layer.

10. The method for preparing the catheter as described in claim 1, characterized in that, A hydrophilic coating is applied to the surface of the finished product, and then UV curing is performed.